Targeting SAMHD1 with the Vpx protein to improve cytarabine therapy for hematological malignancies - Herold, Nikolas; Kutzner, Juliane; Bulli, Lorenzo; Schaller, Torsten (Nature medicine, 2017)
The cytostatic deoxycytidine analog cytarabine (ara-C) is the most active agent available against acute myelogenous leukemia (AML). Together with anthracyclines, ara-C forms the backbone of AML treatment for children and adults1. In AML, both the cytotoxicity of ara-C in vitro and the clinical response to ara-C therapy are correlated with the ability of AML blasts to accumulate the active metabolite ara-C triphosphate (ara-CTP)2,3,4,5, which causes DNA damage through perturbation of DNA synthesis6. Differences in expression levels of known transporters or metabolic enzymes relevant to ara-C only partially account for patient-specific differential ara-CTP accumulation in AML blasts and response to ara-C treatment7,8,9. Here we demonstrate that the deoxynucleoside triphosphate (dNTP) triphosphohydrolase SAM domain and HD domain 1 (SAMHD1) promotes the detoxification of intracellular ara-CTP pools. Recombinant SAMHD1 exhibited ara-CTPase activity in vitro, and cells in which SAMHD1 expression was transiently reduced by treatment with the simian immunodeficiency virus (SIV) protein Vpx were dramatically more sensitive to ara-C-induced cytotoxicity. CRISPR-Cas9-mediated disruption of the gene encoding SAMHD1 sensitized cells to ara-C, and this sensitivity could be abrogated by ectopic expression of wild-type (WT), but not dNTPase-deficient, SAMHD1. Mouse models of AML lacking SAMHD1 were hypersensitive to ara-C, and treatment ex vivo with Vpx sensitized primary patient-derived AML blasts to ara-C. Finally, we identified SAMHD1 as a risk factor in cohorts of both pediatric and adult patients with de novo AML who received ara-C treatment. Thus, SAMHD1 expression levels dictate patient sensitivity to ara-C, providing proof-of-concept that the targeting of SAMHD1 by Vpx could be an attractive therapeutic strategy for potentiating ara-C efficacy in hematological malignancies.